Men's 50km race walk at the 2018 Jakarta Asian Games score analysis - Feng, X.-D.; Sun, J.-N.; Yan, N.; Ding, H.-T.; Hu, G.-S.; Qin, J.-J. (DEStech Transactions on Social Science, Education and Human Science, 2020)
Walking events are the most popular track and field events that win the Olympic Games and World Championships in China. Walking race is a kind of endurance project of technology leading type. As the walking event is judged only by the referee's naked eyes, the skill of the athletes is very important. Once the foul is punished, many years of hard training will disappear. The purpose of this paper is to study and analyze the competition situation of men's 50km walking athletes in the 2018 Jakarta Asian Games, analyze the advantages of foreign athletes, find out the gap with Chinese athletes, and improve the overall level of Chinese men's 50km walking athletes.